The Rapid Adjustment to Tele-analysis and Therapy Due to COVID-19. Issue 1 (1st January 2021) - Prezant, Daniel W.
ABSTRACT: The COVID-19 pandemic resulted in a need to be physically distant from our patients while we were all experiencing a massive life-threatening change in our lives. Analysts and therapists had to stop seeing patients in-person. The overnight shift to teletreatment required many adjustments. This was particularly difficult for child analysis. Exploring these changes allows us to further our understanding of the differences between child and adult analysis as well as to better understand what analysis is.